Perspectives on Public Relations Historiography and Historical Theorization Other Voices - Watson, Tom.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2015)
The National Perspectives on the Development of Public Relations: Other Voices series is the first to offer an authentic world-wide view of the history of public relations. It will feature six books, five of which will cover continental and regional groups. This last book in the series focuses on historiographical and theoretical approaches.
Keywords: International business enterprises; Marketing; Leadership; International economics; Public relations; Development economics; International Business; Marketing; Business Strategy/Leadership.; International Economics; Corporate Communication/Public Relations; Development Economics